2016
DOI: 10.1177/1550059415588658
|View full text |Cite
|
Sign up to set email alerts
|

Is Using Threshold-Crossing Method and Single Type of Features Sufficient to Achieve Realistic Application of Seizure Prediction?

Abstract: Objective This study aims to verify whether the simple threshold-crossing method can work well enough to achieve the realistic application of seizure prediction on the basis of a large public database, and examines how a more complex classifier can improve prediction performance. It also verified whether the combination of multiple types of features with a complex classifier can improve prediction performance. Method Phase synchronization and spectral power features were extracted from electroencephalogram rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…However, multiple features may lead to lower time efficiency. For example, Zheng's study showed that the combination of phase synchronization and spectral power features is unnecessary due to increased computation complexity (Zheng et al, 2016 ). That is, multiple features may not always be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…However, multiple features may lead to lower time efficiency. For example, Zheng's study showed that the combination of phase synchronization and spectral power features is unnecessary due to increased computation complexity (Zheng et al, 2016 ). That is, multiple features may not always be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of a disease can be eventually translated into a classification problem. In this study, in order to verify whether the PSD and non-PSD patients can be distinguished using the extracted brain network characteristics, they were grouped together as the features and the cost-sensitive support vector machine ( Luts et al, 2010 ) was used as the classifier that has been used in our previous studies ( Zheng et al, 2016 ; Zheng and Xu, 2019 ). The classification accuracy defined as the ratio between the number of correctly identified patients and the total number of patients was used as the performance measurement.…”
Section: Methodsmentioning
confidence: 99%
“…In the second step (red boxes in figure 4), real-time decomposition was performed, and the firing rates of N MUs were obtained for individual 0.5 s windows with a 0.1 s step, and were substituted into the regression function (4) to estimate the forces. The estimated force was further smoothed with a Kalman filter, which has been demonstrated to eliminate sporadic, isolated, and large-amplitude fluctuations [38].…”
Section: Data Processing 231 Real-time Force Estimationmentioning
confidence: 99%